Improving Students' Speaking Skills in Indonesian Language Subjects Through The Role-Playing Learning Model for Class 4 SDN Suru Sunda 01 - Febri Isnawati; M. Ilham Rahman Riyadi (Universitas Sebelas Maret, 2020)
This study aims to improve students' speaking skills in Indonesian subjects through role playing learning models in grade 4 SDN Suru Sunda 01. The research method used is Classroom Action Research (PTK) conducted in two cycles. Participants in this study were 4th grade students at SDN Suru Sunda 01 with a total of 25 students. The instruments used in this study were oral tests and observations. The results of the study show that the use of role playing learning models can improve students' speaking skills. In cycle 1, the average percentage of student scores was 70.8% and in cycle 2 it increased to 84.4%. This shows that there is an increase in students' speaking skills in Indonesian through the use of role playing learning models. Thus, it is suggested that teachers be more active in applying the role playing learning model as an alternative to improve students' speaking skills in learning Indonesian.